Management of Entrepreneurial Orientation Tendencies in Artisanal Oil Refineries and Nigeria’s National Growth - Asawo, Soye Peniel (European Scientific Journal, ESJ, 2016)
Nigeria’s oil economy is facing lingering crises and the oil rich Niger Delta region of the country is dotted with illegal artisanal oil refineries with attendant economic, environmental and social consequences for the country. This paper identifies entrepreneurial orientation tendencies exhibited by the operators of these refineries and examines how these tendencies can be managed towards the enhancement of national development. The study adopted the ideographic research methodology, generating textual data from personal observation and series of written reports on the operations of the artisanal oil refineries, and the statements of critical stakeholders including government agents, community leaders and ex-agitators in the Niger Delta region of Nigeria. The qualitative data was analyzed through the use of an issue-focused approach. The study concludes that there is a link between entrepreneurial orientation tendencies and national development and recommends that the Nigerian government should properly manage these entrepreneurial orientation tendencies to enhance national development.